Le autrici e gli autori - Crivelli, Tatiana; Landi, Patrizia; Cherchi, Paolo; Spaggiari, William; Colombo, Paolo; Ciarlantini, Paola; Gioberti, Vincenzo (Rivista Internazionale di Studi Leopardiani, 2022)